Determination of a suitable low‐dose abdominopelvic CT protocol using model‐based iterative reconstruction through cadaveric study. Issue 5 (15th April 2018) - Moloney, Fiachra; Twomey, Maria; Fama, Daniel; Balta, Joy Y; James, Karl; Kavanagh, Richard G; Moore, Niamh; Murphy, Mary Jane; O'Mahony, Siobhan M; Maher, Michael M; Cryan, John F; O'Connor, Owen J
Abstract: Introduction: Cadaveric studies provide a means of safely assessing new technologies and optimizing scanning prior to clinical validation. Reducing radiation exposure in a clinical setting can entail incremental dose reductions to avoid missing important clinical findings. The use of cadavers allows assessment of the impact of more substantial dose reductions on image quality. Our aim was to identify a suitable low‐dose abdominopelvic CT protocol for subsequent clinical validation. Methods: Five human cadavers were scanned at one conventional dose and three low‐dose settings. All scans were reconstructed using three different reconstruction algorithms: filtered back projection (FBP), hybrid iterative reconstruction (60% FBP and 40% adaptive statistical iterative reconstruction (ASIR40)), and model‐based iterative reconstruction (MBIR). Two readers rated the image quality both quantitatively and qualitatively. Results: Model‐based iterative reconstruction images had significantly better objective image noise and higher qualitative scores compared with both FBP and ASIR40 images at all dose levels. The greatest absolute noise reduction, between MBIR and FBP, of 34.3 HU (equating to a 68% reduction) was at the lowest dose level. MBIR reduced image noise and improved image quality even in CT images acquired with a mean radiation dose reduction of 62% compared with conventional dose studies reconstructed with ASIR40, with lower levels of objective image noise, superior diagnostic acceptability and contrast resolution, and comparable subjective image noise and streak artefact scores. Conclusion: This cadaveric study demonstrates that MBIR reduces image noise and improves image quality in abdominopelvic CT images acquired with dose reductions of up to 62%.